Comparative Study of Intra Operative Blood Sugar Level in Spinal Anesthesia and General Anesthesia in Patients undergoing Elective Surgery - Bajracharya, Akriti; Sharma, Surendra Mohan; Bawa, Surinder Nath; Rajbanshi, Lalit Kumar; Arjyal, Batsalya (Birat Journal of Health Sciences, 2018)
Introduction: The aim of the study was to carry out the comparative study of variations in blood glucose levels intra operatively in patients undergoing surgical procedures in Spinal Anesthesia and General Anesthesia by capillary blood glucose level. Objective: To compare intra operative blood glucose level in Spinal and General Anesthesia. Methodology: Sixty non diabetic patients (30 in each group) aged between 20 – 60 years belonging to ASA I and ASA II status were enrolled for this prospective comparative study. Capillary blood glucose was measured preoperatively and thereafter at 15 minutes interval after incision in Spinal Anesthesia and after induction of General Anesthesia till one hour of surgery. For statistical analysis paired sample t – test was used for comparing mean of quantitative data. Difference was considered statistically significant if p < 0.05. Results: Blood sugar level was well controlled in patients receiving spinal anesthesia. General anesthesia produced more increase in blood sugar level compared to base line value which was statistically significant (P<0.05). Similarly, Glycaemia was significantly higher in the General anesthesia group (p < 0.05) when compared with Spinal Anesthesia group suggesting poor control of stress response during general anesthesia. Conclusion: Based on capillary blood glucose level, spinal anesthesia proved more effective in suppressing stress response as compared to general anesthesia in elective surgical patients. BJHS 2018;3(2)6: 458-462